Implementation of Online Ordering and the AIDA Method in the Form of E-Commerce at PT Sleman Nara Group - Muhammad Naufal Arif; Jumi; Mellasanti Ayuwardani (Politeknik Negeri Semarang, 2024)
The application of online marketing using the AIDA method through images, text, and speech can encourage the audience to take action in the form of ordering and expand the company's market reach. In today's dynamic business era, digital marketing plays a crucial role in business development and enhancing marketing quality. PT Sleman Nara Group is an SME engaged in garment production, offering a variety of high-quality clothing. PT Sleman Nara Group currently markets its products offline and has not yet utilized digital platforms, making it difficult to market its high-quality products effectively. The system design approach employs the Waterfall method and the CMS Wordpress as the development tool. The result of this study is an e-commerce website that emphasizes the integration between online and offline stores in terms of product ordering methods, product delivery, product variations, and online services. Additionally, the e-commerce website includes a company profile. The study shows that the e-commerce website can be integrated, allowing purchases to be made anytime and anywhere without needing to visit the offline store. Penerapan pemasaran online menggunakan Metode AIDA melalui gambar, tulisan, dan ucapan dapat mendorong audiens untuk melakukan tindakan pemesanan serta memperluas jangkauan pasar perusahaan. Di era bisnis yang dinamis saat ini, pemasaran digital sangat penting untuk mengembangkan bisnis dan meningkatkan kualitas pemasaran. PT Sleman Nara Group adalah UMKM yang memproduksi garmen. PT Sleman Nara Group memproduksi berbagai jenis pakaian berkualitas. PT Sleman Nara Group memasarkan produknya secara offline dan belum menggunakan platform digital, sehingga mengalami kesulitan dalam memasarkan produk-produknya yang berkualitas. Pendekatan perancangan sistem menggunakan metode Waterfall dan alat CMS Wordpress sebagai aplikasi pengembang. Hasil dari studi ini adalah website e-commerce yang menekankan integrasi antara toko online dan offline pada metode pemesanan produk, pengiriman produk, variasi produk, dan layanan secara online dengan berdasarkan Metode AIDA. Selain itu, website e-commerce ini juga mencakup profil perusahaan. Studi ini menunjukkan bahwa website e-commerce dapat terintegrasi, memungkinkan transaksi pembelian kapan saja dan di mana saja tanpa harus mengunjungi toko offline.